The Role of Organizational Citizenship Behavior, Teamwork, and Organizational Support in Improving Employee Performance - Aldianti, Deni Tri; Ikut, Camilius Isidorus (Faculty of Economics and Business UNTAG Semarang, 2024)
This study aims to determine the influence of Organizational Citizenship Behavior, teamwork, and organizational support in improving employee performance at SMP Negeri 39 Semarang. The population used was all employees of SMP Negeri 39 Semarang with a total of 48 people. The sampling technique used the census, so the sample size used was 48 respondents. The data source used is primary data, with data collection methods using questionnaires. The data analysis technique used is multiple linear regression analysis. The results showed that the role of OCB had a positive and significant effect in improving employee performance, teamwork had a positive and significant effect in improving employee performance and organizational support had a positive and significant effect in improving employee performance. The managerial implication is that employees should be willing to complete tasks outside of their main duties, be cooperative in their work, be open, and prioritize togetherness in the organization.